Pengaruh Penggunaan Software Cabri 3D Terhadap Minat dan Hasil Belajar Matematika pada Pokok Bahasan Bangun Ruang - Ilham Maulana; Saluky Saluky; Muhammad Ali Misri (ITEJ (Information Technology Engineering Journals), 2017)
Advances in technology and information can not be separated from the scope of human life including in education. The quality of education will increase as technology completes education because education will grow in harmony with the development of the world. Therefore, it is necessary to hold learning using technology-based learning media, especially computers. Efforts to use instructional media in the classroom is to use the 3D Cabri Software. This study aims to: 1) To determine the student response to the use of 3D Cabri Software on the subject of wake up space. 2) To know interest and learning result of learning on the subject matter of waking up. 3) To find out how much influence the use of 3D Cabri Software to interest and learning outcomes on the subject of wake up space. Cabri 3D Software is a software geometry that is used for visualization and development of reason to build three-dimensional space, it is expected to be the main capital for learners in improving the intelligence of reasoning and visual spatial. The method used in this research is quantitative method with before-after type with purposive sampling sampling technique. The results showed that: 1) Student response to the use of 3D Cabri software has an average of 67% with good category 2) There is influence of the use of 3D Cabri Software to interest and learning result seen from t test, that is t calculate for learning interest equal to 10,600 And t arithmetic for learning result equal to 10,146 and t table equal to 2,048, then t count > from t table. The interpretation is that there is a significant influence on students' interest and learning outcomes. Student learning outcomes increased as seen from the mean score before using the 3D Cabri software obtained 77.38 and the mean score after using the 3D Cabri software was obtained 82.86. While interest in student learning increased seen from the change of questionnaire of student interest before and after that is equal to 4%. Based on this, the 3D Cabri Software is very feasible and helps to serve as a medium in learning mathematics.